UNDERSTANDING TEACHER PERFORMANCE THROUGH LEADERSHIP ROLE, WORK ENVIRONMENT, AND WORK MOTIVATION - Shanti Auliana; Achmad Sani Supriyanto; Sri Harini (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
Teachers have an essential role in determining the success of education. Teacher performance is of particular concern in the world of education. This study examines the influence of madrasah principal leadership, work environment, and work motivation on teacher performance. The research approach uses a quantitative approach with a correlational type. The population in this study were Madrasah Tsanawiyah Negeri teachers throughout Pidie Jaya Regency, Aceh Province. The sampling technique is purposive sampling. The data collection is a questionnaire measured by a Likert Scale. The validity test was calculated by comparing the r-table at a significant level of 0.05 with degrees of freedom (n-2). The reliability test was carried out using Cronbach Alpha. Data analysis used Partial Least Square to analyze the outer Model, Inner Model, and Bootstrapping. The results showed that the leadership of the madrasah principal had a significant positive effect on work motivation, the work environment has a significant positive impact on teacher work motivation, and the principal’s leadership also has a significant positive impact on teacher performance. The teacher’s work environment has a negative and insignificant effect on teacher performance, while work motivation has a positive and minor impact on teacher performance. Another finding is that there is no indirect effect between the principal’s leadership on teacher performance through work motivation. There is no indirect effect of the work environment on teacher performance through work motivation. Excellent leadership role, well-environment and high work motivation will optimize the teacher performance.